Review of the work The patrimonialization of Archives in Brazil (Interdisciplinary Studies Journal, 2024)
• The book A Patrimonialização Cultural de Arquivos no Brasil (The Cultural Heritage of Archives in Brazil), authored by Francisco Alcides Cougo Júnior, who is from Rio Grande / RS. He is an Assistant Professor in the Department of Archival Studies, Center for Social and Human Sciences (CCSH) at the Federal University of Santa Maria (UFSM). He holds a Ph.D. in Social Memory and Cultural Heritage from the Federal University of Pelotas (2021), a Master's in History from the Federal University of Rio Grande do Sul (2010), a Specialization in Ethics and Education in Human Rights from the Federal University of Rio Grande do Sul (2011), and a Bachelor's degree in Archival Studies from the Federal University of Rio Grande do Sul (2015). He is also a graduate in History – Teaching License from the Federal University of Rio Grande (2008). Between 2004 and 2010, he worked in the areas of History & Music, Human Rights, and Communication.The thesis that resulted in this work used a historical perspective based on a dialectical method, with a qualitative and inductive approach. From a historiographical perspective, it is aligned with Social History, with a focus on the research line of the Social Memory and Cultural Heritage Postgraduate Program, particularly the Politics of Memory and Heritage in MERCOSUR.
Keywords: Archives; Archives Cultural Patrimonialization; Francisco Alcides Cougo Júnior